2023
DOI: 10.3389/fpsyg.2022.999227
|View full text |Cite
|
Sign up to set email alerts
|

“I am feeling tension in my whole body”: An experimental phenomenological study of empathy for pain

Abstract: IntroductionTraditionally, empathy has been studied from two main perspectives: the theory-theory approach and the simulation theory approach. These theories claim that social emotions are fundamentally constituted by mind states in the brain. In contrast, classical phenomenology and recent research based on the enactive theories consider empathy as the basic process of contacting others’ emotional experiences through direct bodily perception and sensation.ObjectiveThis study aims to enrich the knowledge of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 126 publications
(169 reference statements)
0
15
0
Order By: Relevance
“…The analysis focused on the temporal dynamics of the experience. First, we present descriptions of the phenomenological dimensions that emerged in the analysis, followed by the full temporal structure of the empathy experience (a more comprehensive analysis of 28 out of the 35 participants, as well as a review of the codebook, can be found in our previous publication ( Martinez-Pernía et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The analysis focused on the temporal dynamics of the experience. First, we present descriptions of the phenomenological dimensions that emerged in the analysis, followed by the full temporal structure of the empathy experience (a more comprehensive analysis of 28 out of the 35 participants, as well as a review of the codebook, can be found in our previous publication ( Martinez-Pernía et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Accompanying these intentions to act were differing attentional foci—some directed inwardly and others directed outwardly. Both dimensions underscore the intricacies of these phenomena (for more details, see Martinez-Pernía et al, 2023 ) that previous studies, which largely relied on physiological reports and self-reporting, might not have fully captured. Further research could explore the relationship between both experiences and physiological responses.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations